Formation of students' written scientific speech in chemistry: A comparative study of scaffolding strategies - Mitina, Tatyana; Afanasenkova, Irina; Bazarnova, Natalya; Ovchinnikova, Olga; Sheiko, Tatyana (International Journal of Innovative Research and Scientific Studies, 2025)
The development of scientific writing in school chemistry represents a crucial direction in modern pedagogy, aimed at fostering students’ skills in academic argumentation, meaningful structuring of knowledge, and subject-specific language literacy. In this study, we examine various scaffold strategies (cognitive, linguistic, and hybrid) and propose an original model, SWC (Scientific Writing in Chemistry), which integrates pedagogical and cognitive mechanisms for the formation of scientific writing. Our model is based on a seven-step scaffold support algorithm and combines genre-based, process-oriented, and content-language approaches. A comparative theoretical study has been conducted with visual and tabular verification of the SWC model’s effectiveness across key parameters: cognitive load, language support, scientific accuracy, and cross-disciplinarity. We present algorithms, task templates, methodological guidelines, and a risk table. Our findings demonstrate that SWC is a pedagogically balanced and functional model for developing scientific writing in the context of chemistry education.